The intermediate filament protein vimentin is essential for axonotrophic effects of Clostridium botulinum C3 exoenzyme. (9th August 2016) - Adolf, Andrej; Leondaritis, George; Rohrbeck, Astrid; Eickholt, Britta Johanna; Just, Ingo; Ahnert‐Hilger, Gudrun; Höltje, Markus
Abstract : Primary neuronal cultures from vimentin knockout (KO) mice were used to study the impact of vimentin on axonal growth and internalization of C3bot. In contrast to wild type, vimentin knockout neurons were insensitive to the axonotrophic effects of C3bot. Application of extracellular vimentin (recombinant vimentin) to vimentin KO neurons completely restored the growth‐promoting effects of C3bot. In line with this uptake of C3bot into vimentin KO neurons was strongly decreased resulting in reduced ADP‐ribosylation of RhoA and B as detected by an antibody recognizing selectively ADP‐ribosylated RhoA/B. Abstract: The type III intermediate filament protein vimentin was recently identified to mediate binding and uptake of Clostridium botulinum C3 exoenzyme (C3bot) in two cell lines. Here, we used primary neuronal cultures from vimentin knockout (Vim −/− ) mice to study the impact of vimentin on axonal growth and internalization of C3bot. In contrast to wild type, vimentin knockout neurons were insensitive to C3bot. Application of extracellular vimentin to Vim −/− neurons completely restored the growth‐promoting effects of C3bot. In line with this uptake of C3bot into Vim −/− neurons was strongly decreased resulting in reduced ADP‐ribosylation of RhoA and B as detected by an antibody recognizing selectively ADP‐ribosylated RhoA/B. Again, uptake of C3bot into Vim −/− neurons was rescued by addition of extracellular vimentin. In addition, in purified embryonic stem cell‐derived motor neurons that are devoid of glial cells C3bot elicited axonotrophic effects confining neuronal vimentin as a binding partner. Primary neuronal cultures from vimentin knockout (KO) mice were used to study the impact of vimentin on axonal growth and internalization of C3bot. In contrast to wild type, vimentin knockout neurons were insensitive to the axonotrophic effects of C3bot. Application of extracellular vimentin (recombinant vimentin) to vimentin KO neurons completely restored the growth‐promoting effects of C3bot. In line with this uptake of C3bot into vimentin KO neurons was strongly decreased resulting in reduced ADP‐ribosylation of RhoA and B as detected by an antibody recognizing selectively ADP‐ribosylated RhoA/B.